Fast and efficient single step liquid chromatography separation of parent homopolymers from block copolymers - Netopilík, Miloš; Janata, Miroslav; Trhlíková, Olga; Berek, Dušan (Journal of chromatography. A, 2021)
The modified layout of the barrier method called liquid chromatography under limiting conditions of enthalpic interactions is presented. It enables automated quantitative separation of blends of synthetic polymers, for example the single step discrimination of both parent homopolymers from the block copolymers. Moreover, this method enables the estimation of molar mass and molar mass distribution of the block copolymer precursor. Adjacent large sequences of mobile phase of different composition are applied as barriers. They are created by a computer controlled pair of pumping systems in the form of longitudinal profiles along the column. The home synthesized block copolymers polystyrene-block-poly(2-vinylpyridine) served as model examples of the method application. The adsorption retention mechanism was exploited using mesoporous bare silica gel column packing. Series of block copolymers of similar composition can be quickly handled with the method to optimize their synthesis.
Keywords: Adsorption; Molecular Weight; Polymers; adsorpce; Polystyrene-block-poly(2-vinylpyridine); Homopolymers; Barriers; Polystyrenes; Chromatography, Liquid; polymery; Block copolymers; Liquid chromatography under limiting conditions of enthalpic interactions; chromatografie kapalinová; polystyreny; molekulová hmotnost